Demodex sp. Prevalence in patients with blepharitis - Rodríguez Comesaña, Hannali (2000)
OBJECTIVE: To determine the prevalence of Demodex sp. in the hair follicles of patient‘s lashes. Setting: Lima's Laboratory of Microbiology of the National Institute of Ophthalmology (INO), between December ‘97 and February ‘98. MATERIAL AND METHODS: Observational and cross-sectional study. We collected samples of lashes of 196 patients of both sexes, various ages and with symptoms of blepharitis. RESULTS: Fifty-one percent of the patients studied had Demodex sp. in their lashes; 21% of these were between 61-70 year-old; 62% of the positive ones were women and 38% men. The more frequent signs and symptoms were itching (90%), secretion and flashing (80%), vision nuisances (74%), seborrhea (70%), burning (66%), tears shedding (63%), fall of lashes (60%), erithema (39%), chalazion (18%) and edema (11%); acari per field count was high between 5-10 acari per field (28%). CONCLUSIONS: The frequency of Demodex sp. (51%) was high in the study and patient’s age is directly related with the infection.